Association of mycoplasma with prostate cancer: A systematic review and meta-analysis. (December 2021) - Tantengco, Ourlad Alzeus G.; Aquino, Inah Marie C.; de Castro Silva, Mariana; Rojo, Raniv D.; Abad, Cybele Lara R.
Highlights: Prostate cancer patients had 2.24 times higher odds of mycoplasma colonization than benign prostatic hypertrophy (BPH) patients. Prostate cancer patients had 3.6 times increased odds of being colonized with Ureaplasma spp. than BPH patients. This highlights the potential association between chronic mycoplasma infection and prostate cancer. Abstract: Mycoplasmas are emerging sexually transmitted pathogens usually associated with male urinary tract infection, non-gonococcal urethritis (NGU), infertility, and prostate cancer. In this study, we review the evidence linking mycoplasma infection and prostate cancer. We conducted a systematic review and meta-analysis based on PRISMA guidelines. Four electronic databases were reviewed through January 31, 2021. Studies were eligible for inclusion if odds ratio for prevalence or incidence of colonization and/or infection were provided or calculable. All included studies were evaluated independently by three reviewers. The quality of the included studies was assessed using the Newcastle-Ottawa Scale for Case-Control Studies. Statistical analysis was done using Review Manager Version 5.4. A total of 183/744 (24.6 %) patients with prostate cancer compared to 87/495 (17.58 %) patients with benign prostatic hyperplasia (BPH) tested positive for Mycoplasma spp., while 86/666 (12.91 %) and 11/388 (2.84 %) prostate cancer patients and BPH patients, respectively, had Ureaplasma spp. infections. This meta-analysis showed that prostate cancer patients had 2.24 times higher odds (p = 0.0005) of being colonized with any species of Mycoplasma spp. and 3.6 times increased odds (p = 0.008) of being colonized with any species of Ureaplasma spp. In conclusion, patients with prostate cancer were more likely to be colonized with Mycoplasma spp. or Ureaplasma spp. compared to patients with BPH, which highlights the potential association between chronic infection and cancer. However, more studies are needed to determine the specific role that mycoplasma plays in the pathogenesis of prostate cancer.